2023
DOI: 10.1108/jadee-09-2022-0206
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of innovation in the agro-food micro, small and medium enterprises of Uganda

Abstract: PurposeWith focus on Uganda, this study assessed the factors influencing agro-food micro, small and medium enterprises (MSME) innovations. Kampala, Wakiso, Mukono and Jinja districts were the locations of the research.Design/methodology/approachPrimary cross-sectional data was collected using structured questionnaire for a sample of 521 agro-food MSMEs in Uganda. Descriptive statistics, exploratory factor analysis and hierarchical regression analysis were used to examine the data in SPSS.FindingsThe findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The inclusion of rules that encourage and reward creativity would improve customer-focused innovation. Policies and principles that foster innovation and the conduct of internal product and process improvement research, on the other hand, would promote system-focused innovation (Ajer et al, 2023). Moreover, MSMEs should have collaborative and collective problem-solving culture as it contributes more towards innovation (Candra et al, 2021).…”
Section: H41 Top Management and Organization Structure As People-rela...mentioning
confidence: 99%
“…The inclusion of rules that encourage and reward creativity would improve customer-focused innovation. Policies and principles that foster innovation and the conduct of internal product and process improvement research, on the other hand, would promote system-focused innovation (Ajer et al, 2023). Moreover, MSMEs should have collaborative and collective problem-solving culture as it contributes more towards innovation (Candra et al, 2021).…”
Section: H41 Top Management and Organization Structure As People-rela...mentioning
confidence: 99%
“…Customers believed brokers were primarily concerned with closing agreements and didn't care about knowing what their clients needed, based on their research. Numerous studies have examined the connection between client orientation and performance (Abdarpoor & Pakseresht, 2023;Ajer et al, 2023). Empirical study has demonstrated the bene􀅫icial effects of customer orientation on sales performance (Park & Hur, 2023;Varela-Neira et al, 2023;Yousaf et al, 2020) .…”
Section: Customer Orientation and Sales Performancementioning
confidence: 99%
“…Consumer satisfaction and loyalty Kopalle, Kumar, and Subramaniam (2020) and C. M. J. Lee et al (2021) consumer attitudes toward products and salespeople Charoensukmongkol and Pandey (2023), customer repurchase intention Ajer et al (2023), and customer-perceived service quality Mei Jyin et al (2020) are some examples of these outcomes.…”
Section: Customer Orientation and Sales Performancementioning
confidence: 99%
See 2 more Smart Citations